A High-Resolution Tissue-Specific Proteome and Phosphoproteome Atlas of Maize Primary Roots Reveals Functional Gradients along the Root Axes . Issue 1 (16th March 2015) - Marcon, Caroline; Malik, Waqas Ahmed; Walley, Justin W.; Shen, Zhouxin; Paschold, Anja; Smith, Laurie G.; Piepho, Hans-Peter; Briggs, Steven P.; Hochholdinger, Frank
Abstract : Tissue-specific protein and phosphoprotein patterns underlie functional gradients along the maize primary root axis. Abstract: A high-resolution proteome and phosphoproteome atlas of four maize ( Zea mays ) primary root tissues, the cortex, stele, meristematic zone, and elongation zone, was generated. High-performance liquid chromatography coupled with tandem mass spectrometry identified 11, 552 distinct nonmodified and 2, 852 phosphorylated proteins across the four root tissues. Two gradients reflecting the abundance of functional protein classes along the longitudinal root axis were observed. While the classes RNA, DNA, and protein peaked in the meristematic zone, cell wall, lipid metabolism, stress, transport, and secondary metabolism culminated in the differentiation zone. Functional specialization of tissues is underscored by six of 10 cortex-specific proteins involved in flavonoid biosynthesis. Comparison of this data set with high-resolution seed and leaf proteome studies revealed 13% (1, 504/11, 552) root-specific proteins. While only 23% of the 1, 504 root-specific proteins accumulated in all four root tissues, 61% of all 11, 552 identified proteins accumulated in all four root tissues. This suggests a much higher degree of tissue-specific functionalization of root-specific proteins. In summary, these data illustrate the remarkable plasticity of the proteomic landscape of maize primary roots and thus provide a starting point for gaining a better understanding of their tissue-specific functions.